Antibacterial activity of ethanolic Piper cubeba L. extract against Escherichia coli and its effect on microbiological quality of raw chicken meat during storage - Zainalabidin, Fazly Ann; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Piper cubeba L. is traditionally recognised as flavouring ingredient in various types of foods and has been used to marinate meat. Scientifically, it has been reported to possess various valuable nutritional and pharmacological properties including antimicrobial potential. The aim of the present work was to determine the antibacterial activity of ethanolic P. cubeba L. extract against Escherichia coli and its effect on the microbiological quality of raw chicken meat during storage. Disc diffusion assay was done and resulted in 8.40 ± 0.10 mm of inhibition zone. The bacteriostatic and bactericidal effects of the extract were determined at 0.63 ± 0.00 mg/mL and 1.25 ± 0.00 mg/mL of concentration by MIC and MBC methods, respectively. The killing time was recorded at 2 × MIC (1.25 mg/mL) for 4 h. The application of the extract on chicken meat samples showed reduction in TPC and E. coli count with the observed optimum condition at 5.00% concentration stored at -18°C for 14 days based on the consistent reduction. Sensory attributes acceptability evaluation by 9-point hedonic scale showed acceptable score for colour, odour, texture and overall acceptability of the treated raw chicken meat samples. The findings implies that P. cubeba L. can be listed as one of the alternatives to reduce the bacterial load of raw chicken meat prior to cooking which is very important in ensuring food safety as well as reducing the occurrence of foodborne poisoning associated with chicken meat.